PENGARUH KONFLIK INTERPERSONAL ANTAR KARYAWAN TERHADAP KINERJA KARYAWAN PADA PT KEMUNING MITRA PERSADA CABANG SURABAYA III - Mutiara Hati Br Sinuraya; Netty Laura; RutmanLumbantoruan (Universitas Kristen Indonesia, 2023)
The objective of this research is to investigate how interpersonal conflicts impact employee performance within PT Kemuning Mitra Persada Surabaya III Branch. The study utilized a survey approach, employing a questionnaire as the primary tool for data collection. The target population comprised all employees of PT Kemuning Mitra Persada Surabaya III Branch, with a sample size of 80 individuals chosen through proportional random sampling. The data gathering techniques encompassed observation, interviews, questionnaires, and documentation. The collected data underwent analysis, including descriptive analysis, assessment of classical assumptions, and simple regression analysis using SPSS 29 software. The outcomes of the simple regression analysis revealed an equation: Y = 16.019 - 0.555 X, demonstrating a significant negative correlation between interpersonal conflict and employee performance. Essentially, this implies that heightened levels of interpersonal conflict lead to decreased employee performance. The partial hypothesis testing affirmed that interpersonal conflict has an individual, adverse, and statistically significant impact on employee performance. Consequently, it is advisable for PT Kemuning Mitra Persada Surabaya III Branch to conduct regular evaluations of conflict levels within the organization and comprehend their implications for employee performance. Continuous monitoring of conflict situations enables timely identification of emerging issues, facilitating prompt and appropriate action. keywords: interpersonal conflict, employee performance